Flagellate nutritional versatility as a key to survival in two contrasting Antarctic saline lakes - Laybourn-Parry, J; Marshall, WA; Marchant, HJ (2005)
1. Seasonal patterns of grazing and photosynthesis were investigated in two saline Antarctic lakes (Highway and Ace) in the Vestfold Hills (68 degrees S). The phototrophic nanoflagellate (PNAN) community was dominated by Pyramimonas gelidicola and two morphological forms of a cryptophyte species that occurred throughout the year. Both species were mixotrophic on bacteria, and in Highway Lake they also exploited dissolved organic carbon as determined by the uptake of fluorescently labelled dextrans. 2. Clearance rates ranged between 0.02 and 0.21 nL h)1 cell)1 in Ace Lake and 0.004– 1.05 nL h)1 cell)1 in Highway Lake. On occasion cryptophyte grazing equalled that of the heterotrophic nanoflagellates (HNAN). 3. Photosynthetic rates showed similar trends in both lakes, but there were differences in chlorophyll a specific rates and photosynthetic efficiency, probably related to the meromictic characteristic of Ace Lake. Primary production was measurable in winter and peaked in summer following the maxima of mixotroph grazing. 4. The HNAN community of Highway Lake achieved clearance rates of 0.02– 1.80 nL h)1 cell)1 and removing between 50 and 693 ng bacterial carbon L)1 day)1, with highest impact in winter when HNAN were most abundant. The HNAN also ingested fluorescently labelled dextrans showing a preference for 4 and 500 kDa molecules. The more diverse HNAN community of Ace Lake had lower clearance rates (0.04–0.37 nL h)1 cell)1) and exerted a lower grazing pressure on bacterioplankton. In Highway Lake, where the HNAN community was dominated by the choanoflagellate Diaphanoeca grandis, there was a significant correlation between mean cell volume and clearance rate. 5. The major feature was that the microbial plankton functioned throughout the year by employing nutritional versatility.